Juegos de palabras y música en El Cortesano de Luis Milán. - COLELLA, ALFONSO (Scripta, 2015)
This article takes into consideration El Cortesano (1561) by Luis Milán: in this text the musical performance is strongly influenced by the playful attitudes of the individuals who attended the court meetings of Fernando de Aragón and Germana de Foix. Therefore, the musician has to keep in mind every expectation of courtly entertainment and gaming, and morevoer he must open his interpretative options to meet also the demands of the public. What emerges is a picture of the musician and his music that is different from what one would expect in another social context. In such aristocratic society as the Duke of Calabria, music was not understood only in terms of its aesthetic values and technical aspects, but it also required that the player accepted the rituals of the courtly game.